Effects of Soil Compaction and Relative Light Intensity on Survival and Growth Performance of Planted Shorea macrophylla (de Vriese) in Riparian Forest along Kayan Ulu River, Sarawak, Malaysia - Aina Nadia Najwa Mohamad Jaffar; Mohd Effendi Wasli; Mugunthan Perumal; Jonathan Lat; Hamsawi Sani (International Journal of Forestry Research)
A study was conducted in riparian forest along Kayan Ulu River, Sarawak, Malaysia, to investigate the effects of soil compaction and relative light intensity (RLI) on survival and growth performance of planted Shorea macrophylla. The study sites were stands reforested in different years (1996: SPD96; 1997: SPD97; 1998: SPD98; 1999: SPD99). The survival, growth performance, soil compaction, and RLI were measured. SPD96 trees had the highest survival (84%) and showed the most favourable growth. Average height, mean annual increment in height, and RLI were highest in SPD97 while mean annual increment in volume was highest in SPD98. Soil compaction in SPD98 and SPD99 was higher as compared to SPD96 and SPD97. This was due to the compacted soils caused by anthropogenic activities and natural causes (wet soils) in riparian forest along Kayan Ulu River at shallow depth. High survival and favourable growth performance of S. macrophylla were influenced by the edaphic factor with special reference to less compacted soils and high RLI. Stepwise multiple regression demonstrated significant effects of soil penetration resistance at the depth of 0-30 cm and RLI on mean annual increment in diameter. Further ecological studies on other environmental factors should be implemented to draw up a Dipterocarp planting scheme for the future restoration of riparian ecosystem.